Back Cover: Versatile Colorant Syntheses by Multiple Condensations of Acetyl Anilines with Perylene Anhydrides (Angew. Chem. Int. Ed. 7/2015). Issue 7 (13th January 2015) - Jänsch, Daniel; Li, Chen; Chen, Long; Wagner, Manfred; Müllen, Klaus
<x xml:space="preserve">Abstract</x> 100 years ago perylene‐3, 4:9, 10‐tetracarboxylic diimide (PDI) was invented by Kardos and patented as a vat dye by BASF (background left in picture, BASF Ludwigshafen in 1913). In their Communication on page 2285 ff., K. Müllen et al. report versatile synthetic methods to transform PDI into novel chromophores including multiple condensations of acetyl anilines with perylene anhydrides.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>